EL SECUESTRO DE LA POSESIÃ“N DE LOS VEHÃCULOS AUTOMOTORES - Correa Palacio, Ruth Stella; Suarez Hernández, Dr. Daniel; Bermúdez Muñoz, Dr. Martin (Revistas ICDP, 2015)
EL SECUESTRO DE LA POSESIÃ“N DE LOS VEHÃCULOS AUTOMOTORES